More than a Strange Contradiction: Dharma, Colonialism and Agency in Bankimcandra Chatterji's Later Work - Lizotte, Hayden A. (Tufts Archival Research Center, 2015)
This project explores the goals and features of the political and religious program, called dharma, of Bankimcandra Chatterji's later writings. In Chapter 1, I analyze the various influences in colonial Calcutta that would have impacted Bankim, as well as the ways in which new ideas penetrated the colonial milieu and how Enlightenment forms of thought have impacted both the period itself as well as further scholarship on the period. In Chapter 2, I describe the history of the term dharma itself, how Bankim mobilizes the term to fit his own vision of what it should be, and how scholars have misinterpreted his work in a way that erases his agency in the creative construction of new religious ideals. In Chapter 3, I explore the ramifications of Bankim's work for women, and conclude that despite Bankim's representation in his novels of powerful, agentive women, he uses them as tools to advance his vision of dharma rather than as a way to offer substantive change for women.